SAT0065 Effects of Dmard Tapering on Treatment Costs in Rheumatoid Arthritis Patients- An Analysis from The Prospective Randomized Controlled Retro- Study. (15th July 2016) - Hagen, M.; Figueiredo, C.; Cobra, J.F.; Reiser, M.; Haschka, J.; Englbrecht, M.; Hueber, A.; Manger, B.; Kleyer, A.; Finzel, S.; Tony, H.-P.; Wendler, J.; et al.
Abstract : Background: Achieving remission is the most important treatment goal in patients with rheumatoid arthritis (RA). With the development and wider use of highly effective disease modifying anti-rheumatic drugs (DMARD) about half of RA patients reach a state of disease remission, raising the question about tapering or stopping anti-rheumatic treatment. Objectives: To assess the effect of a controlled DMARD tapering regimen on treatment costs and work productivity in RA patients in remission Methods: 101 RA patients in sustained remission (DAS28 <2.6 for more than 6 months) enrolled in the multicenter randomized controlled RETRO Study were analyzed (1). Patients either continued DMARDs (arm1), tapered dose by 50% (arm 2) or entire stopped DMARDs after tapering (arm 3) for one year. Assessment of DMARD costs and work productivity was done every three months in all 101 patients including those remaining in remission and those relapsing a re-starting their original DMARD regimen. Results: In RA patients treated with conventional DMARDs, baseline quarterly treatment costs of 154€ remained stable in arm 1 (156€), while decreasing to 81€ in arm 2 and 75€ in arm 3. In patients treated with biologic DMARDs quarterly treatment costs were 5708€ at baseline. They remained stable in arm1 (5533€) and decreased to 2855€ in arm 2 and 2668€ in arm 3. Overall DMARD costs were reduced by 327.292€ within one year, while outcome was very good with patients either remaining in remission or immediately regaining remission when exposed to original DMARD regimen after relapse. Conclusions: Controlled tapering of DMARD treatment leads to effective reduction of treatment costs in RA patients in sustained remission. References: ) Relapse rates in patients with rheumatoid arthritis in stable remission tapering or stopping antirheumatic therapy: interim results from the prospective randomised controlled RETRO study.Haschka J, Englbrecht M, Hueber AJ, Manger B, Kleyer A, Reiser M, Finzel S, Tony HP, Kleinert S, Feuchtenberger M, Fleck M, Manger K, Ochs W, Schmitt-Haendle M, Wendler J, Schuch F, Ronneberger M, Lorenz HM, Nuesslein H, Alten R, Demary W, Henes J, Schett G, Rech J. Ann Rheum Dis. 2016 Jan;75(1):45–51. doi: 10.1136/annrheumdis-2014-206439. Epub 2015 Feb 6. Disclosure of Interest: None declared